Sofosbuvir/simeprevir versus sofosbuvir/ribavirin regimen in Egyptian patients with hepatitis C virus. Issue 1 (January 2018) - Abdelhakam, Sara M.; Musa, Nevine I.; Sayed, Moataz M.; Saleh, Shereen A.; Rushdy, Marwa
Abstract : Background/aim: Hepatitis C virus (HCV) genotype 4 is the most frequent cause of chronic hepatitis in Egypt. The aim of this study was to compare the efficacy of sofosbuvir/simeprevir for 12 weeks versus sofosbuvir/ribavirin for 24 weeks in Egyptian patients with HCV-related Child A cirrhosis. Methods: Ninety patients with chronic HCV-related Child A cirrhosis whether treatment naive or treatment experienced were included. They were assigned into two groups. Group A included 50 patients who received sofosbuvir 400 mg orally once daily plus simeprevir 150 mg orally once daily for 12 weeks. Group B included 40 patients who received sofosbuvir 400 mg orally once daily plus ribavirin orally twice daily for 24 weeks. Sustained virological response 12 was defined as undetectable HCV-RNA 12 weeks after the completion of therapy. Results: At the end of treatment, HCV RNA was undetectable in 98% in group A and 95% in group B. Sustained virological response 12 was achieved in 90 and 77.5% and the recurrence rate was 8.2 and 18.4% in groups A and B, respectively. There was no significant difference between responders and nonresponders regarding demographic and clinical characteristics except smoking which was less frequent among responders. Baseline HCV RNA was significantly lower among responders in both groups. Conclusion: A 12-week course of sofosbuvir/simeprevir showed a higher response rate than 24 weeks of sofosbuvir/ribavirin among patients with HCV-related Child A cirrhosis.